Toxicity of imidacloprid to the stingless bee Scaptotrigona postica Latreille, 1807 (Hymenoptera: Apidae) - Soares, Hellen Maria [UNESP]; Jacob, Cynthia Renata Oliveira [UNESP]; Carvalho, Stephan Malfitano; Nocelli, Roberta Cornélio Ferreira; Malaspina, Osmar [UNESP] (Springer, 2015)
The stingless bee Scaptotrigona postica is an important pollinator of native and cultivated plants in Brazil. Among the factors affecting the survival of these insects is the indiscriminate use of insecticides, including the neonicotinoid imidacloprid. This work determined the toxicity of imidacloprid as the topical median lethal dose (LD50) and the oral median lethal concentration (LC50) as tools for assessing the effects of this insecticide. The 24 and 48 h LD50 values were 25.2 and 24.5 ng of active ingredient (a.i.)/bee, respectively. The 24 and 48 h LC50 values were 42.5 and 14.3 ng a.i./mu L of diet, respectively. Ours results show the hazard of imidacloprid and the vulnerability of stingless bees to it, providing relevant toxicological data that can used in mitigation programs to ensure the conservation of this species.
Keywords: Acute toxicity; Neonicotinoid; Stingless bee